Pengaruh Struktur Modal, Capital Expenditure, Profitabilitas Dan Kebijakan Dividen Terhadap Nilai Perusahaan Pada Perusahaan BUMN Indonesia. - Mispiyanti Mispiyanti (ITB AAS INDONESIA, 2020)
Some previous studies also show different results (research gap) about the factors that influence the value of the company. This study is to find out how the influence of capital structure, capital expenditure, profitability and dividend policy on corporate value in Indonesian BUMN companies partially and simultaneously. The population in this study is Indonesian BUMN companies that went public during 2015 - 2018 with selected samples based on purposive sampling criteria. The results of this study indicate that capital structure has no effect on the value of Indonesian BUMN companies in the 2015-2018 period, while capital expenditure and dividend policy have a positive effect on firm value and profitability has a negative effect on firm value. This indicates the existence of investment opportunities that attract new investors so they will get high returns. Keywords: BUMN companies, capital structure, capital expenditure, company value, dividend policy, profitability.